2008
DOI: 10.1038/nrn2554
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the developing brain to social signals of emotions

Abstract: PREFACEHumans in diverse cultures develop a similar capacity to recognize the emotional signals of different facial expressions. This capacity is mediated by a brain network that involves emotion-related brain circuits and higher-level visual representation areas. Recent studies suggest that the key components of this network begin to emerge early in life. The studies also suggest that initial biases in emotionrelated brain circuits and the early coupling of these circuits and cortical perceptual areas provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
392
5
10

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 357 publications
(426 citation statements)
references
References 139 publications
(171 reference statements)
19
392
5
10
Order By: Relevance
“…Specifically, prior work has localized the sources of the Nc in anterior cingulate and prefrontal cortex (58), which are brain regions that in adults and young children are strongly interconnected with the amygdala (59) and are viewed as key components of frontolimibic circuits in the human brain. Whereas our results point to a role of the amygdala in the processes observed in the current experiments and are thus principally in support of the view that the amygdala is important for social processing early in development (42)(43)(44), there is no direct evidence for amygdala involvement in our ERP data. Nonetheless, our findings are consistent with accounts that assign a major role to amygdala-prefrontal cortex circuits in the unconscious processing of fear as well as gaze in adults (15,25) and are also in line with developmental models according to which amygdala-prefrontal circuits become functional at around 7 mo of age (43).…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Specifically, prior work has localized the sources of the Nc in anterior cingulate and prefrontal cortex (58), which are brain regions that in adults and young children are strongly interconnected with the amygdala (59) and are viewed as key components of frontolimibic circuits in the human brain. Whereas our results point to a role of the amygdala in the processes observed in the current experiments and are thus principally in support of the view that the amygdala is important for social processing early in development (42)(43)(44), there is no direct evidence for amygdala involvement in our ERP data. Nonetheless, our findings are consistent with accounts that assign a major role to amygdala-prefrontal cortex circuits in the unconscious processing of fear as well as gaze in adults (15,25) and are also in line with developmental models according to which amygdala-prefrontal circuits become functional at around 7 mo of age (43).…”
Section: Discussioncontrasting
confidence: 53%
“…However, it is not until the age of 7 mo that they show a robust attentional bias to fear, as reflected in their neural and behavioral responses (37)(38)(39)(40)(41). The developmental emergence of this fear bias has been linked to the maturation of frontolimbic circuits (42)(43)(44)(45) and occurs at a point in development when infants begin to first experience fear themselves (46,47). Despite our growing understanding of the developmental origins of emotion and gaze processing in humans, some fundamental questions concerning the exact nature of this ability remain unanswered.…”
Section: Significancementioning
confidence: 99%
“…Consistent with evidence that the subcortical pathway for processing emotional stimuli emerged early in phylogenesis, recent evidence in human and non-human primates also indicates that the formation of these same structures is more developed at birth compared to the relatively immature development of the cortical areas involved in visual and emotional processing 113 …”
Section: Comparing Attentional and Sensory Unawarenessmentioning
confidence: 52%
“…Consistent with the proposed role of the subcortical system during development, atypically developing children with autism, who have amygdala dysfunctions 162 , seem to depend more on high spatial frequency aspects for processing faces than typical individuals 163 . As is the case with other development mechanisms in the brain, it is likely that newborns' sensitivity to emotional expressions results from the combination of an experience-independent system -located in subcortical structures -that is biased to process coarse emotional stimuli and experiencedependent factors that promote functional coupling of these structures with visual and attentional areas in the cortex, by refining and stabilizing initially existing cortico-subcortical synaptic connections 113 .…”
Section: Box 3 | Ontogenetic Development Of the Subcortical Pathway Fmentioning
confidence: 99%
“…The ability to recognise emotion in facial expressions is also important for infants to communicate effectively to caregivers, and this represents the emergence of social communication. Numerous behavioural and electrophysiological studies have demonstrated that 5-7-month-old infants can visibly discriminate different facial expressions and exhibit an attention bias towards salient facial expressions (Leppanen & Nelson, 2009). Recent NIRS studies have demonstrated that infants show different haemodynamic responses to different facial stimuli (Nakato et al, 2009(Nakato et al, , 2011a(Nakato et al, , 2011b.…”
Section: Haemodynamic Responses In Infants During Face Recognitionmentioning
confidence: 99%